Assembly and evaluation of an inventory of guidelines that are available to support clinical hematology laboratory practice. (14th May 2015) - Hayward, C. P. M.; Moffat, K. A.; George, T. I.; Proytcheva, M.
Summary: Introduction: Practice guidelines provide helpful support for clinical laboratories. Our goal was to assemble an inventory of publically listed guidelines on hematology laboratory topics, to create a resource for laboratories and for assessing gaps in practice‐focused guidelines. Methods: PubMed and website searches were conducted to assemble an inventory of hematology laboratory‐focused guidelines. Exclusions included annual, technical, or collaborative study reports, clinically focused guidelines, position papers, nomenclature, and calibration documents. Results: Sixty‐eight guidelines were identified on hematology laboratory practice topics from 12 organizations, some as joint guidelines. The median year of publication was 2010 and 15% were >10 years old. Coagulation topics had the largest numbers of guidelines, whereas some areas of practice had few guidelines. A minority of guidelines showed evidence of periodic updates, as some organizations did not remove or identify outdated guidelines. Conclusions: This inventory of current practice guidelines will encourage awareness and uptake of guideline recommendations by the worldwide hematology laboratory community, with the International Society for Laboratory Hematology facilitating ongoing updates. There is a need to encourage best guideline development practices, to ensure that hematology laboratory community has current, high‐quality, and evidence‐based practice guidelines that cover the full scope of hematology laboratory practice.